The Effect of The Model S.B.L on The achievement of Fifth Grade Primary school Female in mathematics (Journal of the College of Basic Education, 2024)
The research objective To identify the impact of the S.B.L model on the achievement of fifth grade students in mathematics, the semi-experimental approach was adopted to achieve the research goal, and the research sample was deliberately chosen and consisted of (51) female students (after excluding the failing students) from the fifth grade students at the (Hajar Primary School for Girls) of the General Directorate of Diyala Education / Muqdadiya District, for the first semester of the academic year (2022-2023) AD, and the two research groups were rewarded in some variables. The research tool (achievement test) was prepared according to the first three levels (knowledge, comprehension, application) for Bloom's classification of the field of knowledge, as the test consisted of (20) objective items of the type (multiple choice) and its validity and stability were calculated. After completing the application of the experiment, the test was applied to the research sample, and after collecting data and processing it statistically using the statistical package SPSS, the results showed a difference in favor of the experimental group students in the achievement test